2022
DOI: 10.1002/cbic.202200090
|View full text |Cite
|
Sign up to set email alerts
|

Switchable DNA‐Based Peroxidases Controlled by a Chaotropic Ion**

Abstract: Here we demonstrate a switchable DNA electron‐transfer catalyst, enabled by selective destabilization of secondary structure by the denaturant, perchlorate. The system is comprised of two strands, one of which can be selectively switched between a G‐quadruplex and duplex or single‐stranded conformations. In the G‐quadruplex state, it binds hemin, enabling peroxidase activity. This switching ability arises from our finding that perchlorate, a chaotropic Hofmeister ion, selectively destabilizes duplex over G‐qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…This structure can bind heme (Extended Data Fig. 5a), catalyzing the same peroxidase reactions as HRP, which we have previously demonstrated in high-perchlorate solutions using DNA 41 . We observed these reactions also occur in the RNA context with the RNA G quadruplex rPS2.M ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 68%
“…This structure can bind heme (Extended Data Fig. 5a), catalyzing the same peroxidase reactions as HRP, which we have previously demonstrated in high-perchlorate solutions using DNA 41 . We observed these reactions also occur in the RNA context with the RNA G quadruplex rPS2.M ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 68%
“…We observed that these reactions also occur in the RNA context with the RNA G quadruplex rPS2.M even in near-saturated perchlorate solutions of 8 M (Supplementary Fig. 7b) 46,47 . Motivated by these findings, we hypothesized that this same RNAzyme could also catalyze halogenation reactions.…”
Section: Perchlorate (Clo 4 -mentioning
confidence: 72%
“…In conclusion, it is possible that iron porphyrins already played a role in prebiotic times on the early Earth, possibly as ROS (and RSS)-degrading enzyme-like systems formed with amphiphile aggregates, well before the suggested formation of the more complex hemin-G-quadruplex RNA structures. 26b, 169 Obviously, micelle-forming amphiphiles are chemically much simpler than oligonucleotides with a specific sequence.…”
Section: Prebiological Considerationsmentioning
confidence: 99%